CACTIN is an essential nuclear protein in Arabidopsis and may be associated with the eukaryotic spliceosome. Issue 7 (27th February 2013) - Baldwin, Katherine L.; Dinh, Elizabeth M.; Hart, Brian M.; Masson, Patrick H.
Abstract : ATG7 physically interacts with ATG12A by two hybrid (View Interaction: 1, 2) Abstract : ► ctn‐1 Arabidopsis mutants arrest as very early embryos. ► CACTIN‐RFP rescues ctn‐1 and localizes to the nucleus. ► CACTIN‐RFP colocalizes with spliceosome components. ► CACTIN binds to, and colocalizes with, AT5G63440: a putative spliceosome component. ► CACTIN may play a role in the spliceosome.